Hypouricemic Effects of Extracts From Agrocybe aegerita on Hyperuricemia Mice and Virtual Prediction of Bioactives by Molecular Docking - Yong, Tianqiao; Chen, Shaodan; Xie, Yizhen; Shuai, Ou; Li, Xiangmin; Chen, Diling; Su, Jiyan; Jiao, Chunwei; Liang, Yalei (Frontiers in Pharmacology, 2018)
Agrocybe aegerita has long been utilized for promoting diuresis in traditional Chinese medicine (TCM) with a close correlation to hypouricemia. Ethanol (AAE) and water (AAW) extracts of the compound led to a remarkable decrease in serum uric acid levels (SUA) in hyperuricemia mice, approaching that of the normal control. Both AAE and AAW exhibited suppression effects on hepatic xanthine oxidase (XOD) activities and elevation effects on renal OAT1 (organic anion transporter 1). However, only little negative impact was observed on the inner organ functions. The molecular docking was used to screen our in-home compound database for A. aegerita, and four compounds including 2-formyl-3,5-dihydroxybenzyl acetate, 2,4-dihydroxy-6-methylbenzaldehyde, 2-(6-hydroxy-1H-indol-3-yl)acetamide, and 6-hydroxy-1H-indole-3-carbaldehyde (HHC) were identified as potential active compounds. Their inhibitory mechanism on XOD might be attributed to their localization in the tunnel for the entrance of substrates to XOD active site, preventing the entrance of the substrates. To confirm the activity of the screened compounds experimentally, HHC was selected due to its high ranking and availability. The assaying result suggested the significant inhibitory activity of HHC on XOD. Also, these compounds were predicted to carry good ADME (absorption, distribution, metabolism, and excretion) properties, thereby necessitating further investigation. The current results provided an insight into the hypouricemic effects of macrofungi and their bioactives, which might provide the significant theoretical foundation for identifying and designing novel hypouricemia compounds.